Кількісні характеристики темпоральних прислівників-антонімів - Гончарук (Бєлова), Світлана Вікторівна; Honcharuk (Byelova), S. V. (Волинський національний університет імені Лесі Українки, 2008)
Стаття присвячена дослідженню кількісних характеристик темпоральних прислівників-антонімів. Автор аналізує абсолютні частоти членів антонімічних пар за допомогою статистичних методів. The article is devoted to the investigation of quantitative characteristics of temporal adverbs-antonyms. The author analyses absolute frequencies of the members of antonymous pairs with the help of statistical methods.
Quantitative characteristics of temporal adverbs-antonyms
Keywords: абсолютна частота; absolute frequency; хі-квадрат; chi-square; кореляційний аналіз.; correlation analysis